ANALISIS KESULITAN BELAJAR SISWA BERKEMAMPUAN MATEMATIKA RENDAH BERDASARKAN GENDER - Aini, Septi Dariyatul; Zayyadi, Moh; Hasanah, Anisatul (Kadikma, 2021)
This study aims to fully describe the learning difficulties of students with low mathematical abilities in solving arithmatic division operations based on gender. This research is a descriptive qualtative research with research subjects consisting of 1 female student and 1 male student with low math ability in class IV-A SDN Bugih 1 Pamekasan with the test instrument for the comlpetion of the division count operations aninterviews. The results showed that on thr indicators of difficulty in understanding the concept, the results of the study learning difficulities in female subject (S1) and male subject (S2) in solving the division arithmetic operation, namely the two subjects did not know the concept of division as repeated subtraction. On the indicator of difficulty in applying the principle, the two subjects were unable to do the tiered division correctly because the wo principle of division to the long division. Whereas in the indicator of difficulty in solving verbal problems, the two subjects were unable to write down what wa known and what was asked of the story problem correclty.